2012
DOI: 10.1596/26782
|View full text |Cite
|
Sign up to set email alerts
|

How Much Does Utility Access Matter for the Performance of Micro and Small Enterprises?

Abstract: The empirical evidence of the economic benefits of different utilities such as electricity, telecommunications and water is mixed and, in the case of micro and small enterprises, relatively thin. This paper therefore revisits this issue. Based on a unique, albeit crosssectional, micro data set of informal firms in West-Africa, we find hardly any evidence for a significant contribution of access to different infrastructure services on enterprise performance. This absence of a systematic influence is attributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Generally the results suggest that those who aim to achieve higher satisfaction for business owners, employees and customer etc should consider access to electricity supply and firm age. These results are certainly in parallel with prior writings on the importance of electricity supply and SMEs performance such as Fadderke and Bogetic (2006); Grimm et al (2012) and Kirubi et al (2009).…”
Section: Discussion Of Findingssupporting
confidence: 83%
See 1 more Smart Citation
“…Generally the results suggest that those who aim to achieve higher satisfaction for business owners, employees and customer etc should consider access to electricity supply and firm age. These results are certainly in parallel with prior writings on the importance of electricity supply and SMEs performance such as Fadderke and Bogetic (2006); Grimm et al (2012) and Kirubi et al (2009).…”
Section: Discussion Of Findingssupporting
confidence: 83%
“…Furthermore, Kirubi et al (2009)analysed community-based micro-girds in rural Kenya, and showed that use of electricity can increase productivity per worker by approximately 100-200% for carpenters and by 50-170% for tailors, depending on the item being produced. In another study, Grimm et al (2011) found that tailors in Burkina Faso with access to electricity have revenues 51% higher than tailors without electricity, and attribute this to the use of electric sewing machines and longer working hours. Although the evidence shows a correlation between electricity consumption and firm productivity, and firms with access to electricity tend to have higher productivity than firms without, establishing causality is complex.…”
Section: Review Of Empirical Literaturementioning
confidence: 99%
“…Some studies suggest that electricity has limited impact on increasing the income of microenterprises and small enterprises. Grimm, Hartwig, and Lay (2011) found that electricity supply had no systematic or uniform influence on the profits of small tailoring businesses in Ouagadougou, Burkina Faso. In fact, they concluded that the supply of electricity could be a financial burden because of the high cost of grid connection and electrical appliances.…”
Section: Review Of Productive Use Literaturementioning
confidence: 88%
“…As mentioned, access to energy is a basic ingredient for development and is significantly associated with poverty reduction via productivity, income growth, health and education, gender, social impacts of energy extraction, human development, and via macroeconomic stability and governance (World Bank 2001). Only a few empirical studies have examined the impact of electricity access on poverty reduction (Balisacan 2001;Fan et al 2000Fan et al , 2002; on productivity (Barnes and Binswanger 1986;Escribano et al 2009); on employment (Kooijman-van Dijk 2008Goedhuys and Sleuwaegen 2010;Dinkelman 2008) and on household income (Grimm et al 2011;Fan et al 2005;ESMAP 2005).…”
Section: Literature Reviewmentioning
confidence: 99%